Stand for Experimental Evaluation of Effects of Hydrogen Use in Internal Combustion Engines - Levente B.; Lelea D.; Birsan N. (Problems of the Regional Energetics, 2015)
Hydroxy gas or the Brown gas or simply HHO, as it is called more often now days, is a highly flammable gas that has been around since the beginning of the XX-th century, when scientist Yull Brown has dedicated his work to study the properties and means of production of HHO by water electrolysis. In the second half of the century, the oil crisis, the simplicity of HHO production and its high combustion temperature and flame propagation have spurred the interest of ”garage inventors” around the world, who started doing practical experiments with HHO injection on personal vehicles and power-generators, in trying to reduce gas mileage, increase the engine performance and lower tailpipe emissions. Today, this technology is being rediscovered, again due to higher fuel prices and this time also due to some increasing concerns over global warming. Many have learned that HHO injection into the IC engine improves the gas mileage and reduces emissions, some reporting fuel savings of up to 40%, while others even claim to have reached the performance of operating their engines on HHO entirely produced onboard of the running vehicle. There are also reports that claim increased life span of the engine and engine lubrication, due to reduction effect of HHO on the solid hydrocarbon depositions onto the engine critical components, like pistons, valves, cylinder walls, etc. In this regard, the University Politehnica Timisoara Department of Mechanical Machines, Equipment and Transportation and Department for Applied Chemistry and Engineering of Inorganic Compounds and Environment, have joined together in a project to study and understand the mechanism that take place during HHO injection to IC engines, quantify the benefits and develop safer, better and more reliable materials for HHO on-demand and on-board production by water electrolysis.